Different Growth Partitioning and Shoot Production of Talinum triangulare Treated with Organic and Inorganic Fertilizer - Aziz, Sandra A.; Mualim, Leo; Farchany, Sitta Azmi (Journal of Tropical Crop Science, 2014)
Talinum triangulare or waterleaf is an underutilized tropical plant, mostly found as weeds, and has been used more as medicinal plant than as vegetable in Indonesia.  The study of Talinum triangulare cultivation has been explored to increase the shoot production as functional vegetables.  The effects of organic fertilizer applications   at 0.50, 0.75, 1.00, 1.25 and 1.50 of the standard rate on waterleaf growth were tested in a Leuwikopo research station, Bogor, West Java, Indonesia. Standard rate of organic fertilizer consisted of 12.3 t..ha-1 of cow manure, 226.8 kg. .ha-1 of guano, and 5.5 t.ha-1 of rice hull ash that is equal to 100 kg urea, 60 kg SP-36 and 100 kg KCl.ha-1.  Net assimilation rate (NAR) of the organic fertilizer-treated plants was lower than the inorganic fertilizer-treated with plant at two to four weeks after planting (WAP). However, the plants treated with 0.75-1.25 organic fertilizer had a higher NAR than those treated with inorganic fertilizer at four to six WAP.  Plants treated with 0.75 rate of organic fertilizer had similar relative growth rate (RGR) to plants treated with the inorganic fertilizer at two to four WAP, whereas plants treated with 1.00, 1.25 and 1.50 standard rate had higher RGR than plants treated with inorganic fertilizer at 4-6 WAP.   Plants treated with 1.50 organic fertilizer rate had 34.55% more marketable shoots compared to those treated with inorganic fertilizer whereas those treated with 0.50 rate of organic fertilizer had 179.54% at 6 WAP.  The percentage of marketable shoots to total fresh weight of the organic fertilizer-treated plants was lower than the inorganic fertilizer-treated plants.Keywords: Talinum triangulare, leafy vegetables, organic